Saltwater Intrusion into Coastal Aquifers and Associated Risk Management: Critical Review and Research Directives - Basack, Sudip; Loganathan, M.K.; Goswami, Ghritartha; Khabbaz, Hadi (Journal of coastal research, 2022)
Basack, S.; Loganathan, M.K.; Goswami, G., and Khabbaz, H., 2022. Saltwater intrusion into coastal aquifers and associated risk management: Critical review and research directives. Journal of Coastal Research, 38(3), 654–672. Coconut Creek (Florida), ISSN 0749-0208. Coastal regions mainly rely on sources of local fresh groundwater for domestic, irrigational, and industrial usages, which are vulnerable to high-risk of getting intruded by saltwater. Excessive pumping of fresh groundwater initiates advances of saltwater-freshwater interface inward due to hydraulic equilibrium and continuity. This introduces saline water intrusion into coastal aquifers. This is also caused by natural hazards like sea-level rise and storm-surge. The saltwater intrusion in coastal aquifers contaminates the freshwater storage, thereby emerging as a major environmental issue. To incorporate adequate coastal groundwater control and management techniques that are effective and conveniently implementable, understanding the phenomenon of saline water intrusion and the risk assessment is of utmost importance. Several scientific contributions including theoretical (analytical and numerical) solutions, experimental (laboratory and field) results, design recommendations, and risk analysis are available, indicating remarkable advances in the research area. The authors have attempted to summarize the significant contributions over the last few decades in each of these study aspects through extensive literature survey and critical analysis of the existing knowledge. It is observed that risk prevention and control methodologies such as qanat-well structure, shallow and deep wells might not be effective in many coastal areas as the complex intrusion process is yet to be understood clearly. Moreover, the high intensity coastal hazards that often occur due to climate change continue to make aquifers more vulnerable, adversely affecting the coastal groundwater management. The paper presents a critical overview of existing studies on saline water intrusion into coastal aquifers and associated risks and management techniques. Furthermore, adequate research directives with recommendations for future development are also provided.